Determinants of climate change adaptation: evidence from household farmers in Sumenep Regency, East Java - Mardiyah Hayati; Mohammad Wahyu Firdaus; Taufik Rizal Dwi Adi Nugroho; Desi Ramadhani; Risma Nabila; Moh. Rizal; Syauqi Agung Firmanda (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
Climate change poses serious challenges to agricultural production, particularly for smallholder farmers who depend on climate-sensitive farming systems. Increasing climate variability, irregular rainfall patterns, and prolonged dry seasons have heightened the vulnerability of agricultural activities, especially in dryland areas. This study aims to identify climate change adaptation strategies adopted by household farmers and analyze the factors influencing their adoption in Sumenep Regency, East Java. Primary data were collected from 120 farmers using a multistage sampling technique through structured interviews covering farmers’ socio-economic characteristics and adaptation practices. Descriptive statistical analysis was used to identify the types of adaptation strategies implemented by farmers, while a Multivariate Probit model was applied to examine the determinants of farmers’ adoption decisions. The results show that farmers implement several adaptation strategies with different adoption levels. Crop rotation is the most widely adopted strategy, followed by adjusting planting times and using climate-resistant crop varieties. In contrast, water-saving irrigation is the least adopted strategy due to limited irrigation infrastructure. The econometric results indicate that farming experience, participation in farmer groups, and access to mobile banking significantly influence farmers’ decisions to adopt climate adaptation strategies. Strengthening farmer institutions, improving financial inclusion, and enhancing agricultural extension services are therefore crucial to improve farmers’ adaptive capacity and promote more resilient agricultural systems in climate-vulnerable regions.